Validation of a HPLC/FLD method for quantification of tocotrienols in human plasma - Che, Hui Ling; Tan, Doryn Meam Yee; Meganathan, Puvaneswari; Gan, Yee Lin; Abdul Razak, Ghazali; Fu, Ju Yen (Hindawi Publishing Corporation, 2015)
Quantification of tocotrienols in human plasma is critical when the attention towards tocotrienols on its distinctive properties is arising. We aim to develop a simple and practical normal-phase high performance liquid chromatography method to quantify the amount of four tocotrienol homologues in human plasma. Using both the external and internal standards, tocotrienol homologues were quantified via a normal-phase high performance liquid chromatography with fluorescence detector maintained at the excitation wavelength of 295 nm and the emission wavelength of 325 nm. The four tocotrienol homologues were well separated within 30 minutes. A large interindividual variation between subjects was observed as the absorption of tocotrienols is dependent on food matrix and gut lipolysis. The accuracies of lower and upper limit of quantification ranged between 92% and 109% for intraday assays and 90% and 112% for interday assays. This method was successfully applied to quantify the total amount of four tocotrienol homologues in human plasma.